DIAGNOSA VIBRIO CHOLERAE DENGAN METODE KULTUR DAN PCR PADA SAMPEL SUMBER AIR MINUM - Yusnita, Desi; Krisdianilo, Visensius (Jurnal FARMASIMED (JFM), 2021)
Acute diarrhea due to infection can be caused by a bacterial, viral or parasitic infection. One of the bacteria that causes diarrhea is Vibrio cholerae and usually the diarrhea caused is called cholera diarrhea. Cholera diarrhea is caused by enterotoxins produced by V. cholerae bacteria and forms colonies inside the small intestine. Symptoms include vomiting, defecation such as large amounts of rice water resulting in dehydration, electrolyte loss and increased blood acidity. In severe cases, the sufferer continuously defecates accompanied by vomiting, so that the sufferer will lose fluids and electrolytes quickly from the gastrointestinal tract. This leads to a rationing of metabolic acidity and when left untreated can lead to death. V. cholerae bacteria are not invasive, do not enter the bloodstream but remain in the intestinal tract. At the time of infection through contaminated food and beverages ingested, then after passing through the stomach acid defense V. cholerae produces two virulence factors that cause cholera, namely coregulated pilus toxin (TCP) and cholera toxin (CT). The existence of specific enterotoxin cholera only found in V. cholerae pathogens can be targeted in laboratory tests for the diagnosis of pathogenic V. cholerae bacteria using biomolecular techniques such as polymerase chain reaction (PCR) methods. From the results of the examination of drinking water samples at the drinking water depot around the bottom of the pakam, obtained the results of the PCR examination confirmed by electrophorensis is 302 bp, which means that in the sample there are bacteria that are identic with Vibrio cholera.